Does Preexisting Practice Modify How Video Games Recalibrate Physician Heuristics in Trauma Triage? - Kulkarni, Shreyus S. (J Surg Res, 2019)
BACKGROUND: A majority of severely injured patients fail to receive care at trauma centers (undertriage), in part, because of physician judgment. We previously developed two educational video games that reduced physicians’ undertriage compared with control in two clinical trials. In this secondary analysis, we investigated heterogeneity of treatment effect of the interventions by assessing physicians’ preexisting practice patterns in claims data. We hypothesized that physicians with high preexisting undertriage would benefit most from game-based training. METHODS: Using Medicare claims records from 2010 to 2015, we measured physicians’ preexisting triage practices before their participation in one of two trials conducted in 2016 and 2017. We categorized physicians as having received game-based training versus control and noted their postintervention simulation triage performance in the trials. We used multivariable linear regression models to assess the heterogeneity of game-based training effect among physicians with high and low preexisting undertriage. RESULTS: Of the 394 eligible physicians from our trials, we identified 275 (70%) with claims for Medicare fee-for-service beneficiaries suffering severe injury between 2010 and 2015. On average, the physicians were 44 y old (SD 8.4) with 12 y (SD 8.2) of experience. We found significant interaction between preexisting practice and intervention efficacy (P = 0.04). Physicians with high undertriage before enrollment improved significantly with game-based training compared with the control (46% versus 63%, P < 0.001). Those with low preexisting undertriage did not (58% versus 56%, P = 0.76). CONCLUSIONS: Using claims-based data, we found heterogeneity of treatment effect of interventions designed to recalibrate physician heuristics. Physicians with high preexisting undertriage benefited most from game-based training.